Effect of community participation on sustainable development: an assessment of sustainability domains in Malaysia - Marzo, Roy Rillera; Chen, Hana W. Jun; Anuar, Haryati; Abdul Wahab, Mohamad Khairuddin; Ibrahim, Mohd Hairulnizam; Ariffin, Indang Ariati; Ahmad, Azral Ismawy; Kawuki, Joseph; Aljuaid, Mohammed (Frontiers in Environmental Science, 2023)
ABSTRACT: Introduction: Community participation is also one of the critical factors, in the success of coral reef conservation efforts in Malaysia. The key determinants of community participation in coral reef conservation in the country include awareness, understanding, benefits, and incentives. Objectives: The study aimed to investigate the impact of community participation on sustainable development in Malaysia, specifically in coral reef conservation. The study assessed the relationships between sociodemographic variables and various sustainability domains, including community participation, ecotourism development, and economic, environmental, and social sustainability. Methods: This was a cross-sectional study conducted from July to October 2022 in Setiu, Terengganu and recruited 338 adult local villagers. Bivariable and multivariable logistic regression analysis, factors such as employment status, knowledge of coral reefs, practice of coral reef conservation and willingness to volunteer for conservation were analysed using SPSS version 26. Results: An increase in community participation was associated with an increase in all four sustainability domains of ecotourism development, economic, environmental and social sustainability (Unadjusted B range = 0.46-0.77, all p-value <0.001). Participants with acceptable knowledge of coral reefs (AOR=7.11, 95%CI: 3.84-13.15), good practice of coral reef conservation (AOR=5.26, 95%CI: 2.54-10.91), and willing to volunteer for coral reef conservation (AOR=1.98, 95%CI: 1.02-3.83) had higher odds of positive social sustainability, compared to those with low knowledge, poor practice and not willing to volunteer, respectively. However, those employed in marine-related jobs (AOR=0.27, 95%CI: 0.10-0.72) had less odds of positive social sustainability, compared to those who are not employed. Conclusion: The study highlighted the importance of community participation in promoting sustainable development and the influence of socioeconomic factors and education on community participation. The importance of educational initiatives and engagement and the factors associated with positive economic, environmental and social sustainability have been highlighted. These findings can be used by policymakers and stakeholders to design and implement effective interventions for coral reef conservation, aimed at promoting sustainable development in Malaysia.